MUC4 mucin- a therapeutic target for pancreatic ductal adenocarcinoma. (3rd July 2017) - Gautam, Shailendra K.; Kumar, Sushil; Cannon, Andrew; Hall, Bradley; Bhatia, Rakesh; Nasser, Mohd Wasim; Mahapatra, Sidharth; Batra, Surinder K.; Jain, Maneesh
ABSTRACT: Introduction : Pancreatic cancer (PC) is characterized by mucin overexpression. MUC4 is the most differentially overexpressed membrane-bound mucin that plays a functional role in disease progression and therapy resistance. Area covered : We describe the clinicopathological significance of MUC4, summarize mechanisms contributing to its deregulated expression, review preclinical studies aimed at inhibiting MUC4, and discuss how MUC4 overexpression provides opportunities for developing targeted therapies. Finally, we discuss the challenges for developing MUC4-based therapeutics, and identify areas where efforts should be directed to effectively exploit MUC4 as a therapeutic target for PC. Expert opinion : Studies demonstrating that abrogation of MUC4 expression reduces proliferation and metastasis of PC cells and enhances sensitivity to therapeutic agents affirm its utility as a therapeutic target. Emerging evidence also supports the suitability of MUC4 as a potential immunotherapy target. However, these studies have been limited to in vitro, ex vivo or in vivo approaches using xenograft tumors in immunodeficient murine models. For translational relevance, MUC4-targeted therapies should be evaluated in murine models with intact immune system and accurate tumor microenvironment. Additionally, future studies evaluating MUC4 as a target for immunotherapy must entail characterization of immune response in PC patients and investigate its association with immunosuppression and survival.